Recent Developments in Direct C–H Functionalization of Quinoxalin-2(1H)-ones via Radical Addition Processes - Monika, Monika; Selvakumar, Sermadurai (Synthesis, 2019)
This review article covers the recent developments in direct C–H functionalization of quinoxalin-2(1H)-one derivatives via radical additions at the C3 position. Reaction types have been categorized depending on the kind of radical used, with representative examples and insightful mechanistic details provided.1 Introduction2 Reactions with Alkyl Radicals3 Reactions with Acyl Radicals4 Reactions with Aryl Radicals5 Reactions with Perfluoroalkyl Radicals6 Reactions with Alkoxycarbonyl Radicals7 Reactions with Nitrogen Radicals8 Reactions with Oxygen Radicals9 Reactions with Phosphorus Radicals10 Conclusion
Keywords: C–H functionalization; quinoxalin-2(1H)-ones; visible light photocatalysis; radicals; oxidants